2011
DOI: 10.9749/jin.124.103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Positioning Performance for RTK-GPS/GLONASS with Calibrated Inter-channel Hardware Biases

Abstract: The purpose ofthis paper is to improve GLONASS positioning perfbrmance in RTK − GPSIGLONASS between different types of receivers . Tables。f inter − channel code biases in various receivers were obtained with a zero baseline test in order to examine the magnitude of inter − channel code bias between the receivers . We showed the improvement of fix rate and positioning accuracy of RTK − GPSIGLONASS between diffbrent types of receivers by using table ofthe calibrated GLONASS biases and partial ambigUity fixing so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…With respect to the GLONASS system, the DISB has an apparent linear relationship with the receiver pair JAVAD-TRIMBLE and SEPTENTRIO-TRIMBLE. In the study of Yamada et al (2010), the code inter-channel bias of the L1 band also shows similar phenomena for the receiver pair NOVATEL-TRIMBLE, NOVATEL-JAVAD and NOVATEL-TOPCON. We propose using Equation (7) in DGNSS positioning including the GLONASS system for receiver pairs showing similar characteristics.…”
Section: New Combined Dgnss Model and Positioning Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…With respect to the GLONASS system, the DISB has an apparent linear relationship with the receiver pair JAVAD-TRIMBLE and SEPTENTRIO-TRIMBLE. In the study of Yamada et al (2010), the code inter-channel bias of the L1 band also shows similar phenomena for the receiver pair NOVATEL-TRIMBLE, NOVATEL-JAVAD and NOVATEL-TOPCON. We propose using Equation (7) in DGNSS positioning including the GLONASS system for receiver pairs showing similar characteristics.…”
Section: New Combined Dgnss Model and Positioning Resultsmentioning
confidence: 52%
“…In general, the receiving equipment of the same type experiences similar inter-channel biases, which can be removed to a large extent in the differential mode (Zinoviev 2005). However, as more and more manufacturers have entered the GPS/GLONASS receiver market, GLONASS receivers from different manufacturers today show large differences in their inter-channel biases (Wanninger 2012; Yamada et al, 2010). Therefore, Equation (5) similarly presents the observational formula of GLONASS for a rover segment, where r refers to a particular GLONASS satellite, and k denotes the channel number.…”
Section: Methods Of Evaluating the Isb In The Dgnss Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the GLONASS system adopts the signal pattern of frequency division multiple access, the inter-frequency code bias (IFCBs) and the inter-frequency carrier phase bias (IFPB) will affect the MW combination observations and will further influence the wide-lane ambiguity fixing. Scholars have comprehensively studied the characteristic of inter-frequency bias and its influence on GLONASS ambiguity fixing 17 18 19 20 21 22 . Their results show that the IFPB is mainly related to the receiver type and has a linear relation with frequency.…”
mentioning
confidence: 99%
“…Residual error can be reduced to a few millimeters after calibration and has hardly influence on wide-lane ambiguity fixing. However, no obvious linear relationship exists between the IFCBs and the frequency; hence, no unified and effective correction model is known 18 23 24 25 26 . Reussner and Wanninger indicated that IFCBs are difficult to correct.…”
mentioning
confidence: 99%